Framework conditions facilitating paediatric clinical research - Alfarez Deborah; Bácsy Ernö; Lutsar Irja; Alberighi Ornella; Bauzon Stéphane; Knellwolf Anne-Laure; Panei Pietro (BMC, 2011)
Abstract The use of unlicensed and "off-label" medicines in children is widespread. Between 50-80% of the medicines currently administered to children have neither been tested nor authorized for their use in the paediatric population which represents approximately 25% of the whole European population. On 26 January 2007, entered into force the European Regulation of Paediatric Medicines. It aims at the quality of research into medicines for children but without subjecting the paediatric population to unnecessary clinical trial. This article addresses ethical and legal issues arising from the regulation and makes recommendations for the framework conditions facilitating the development of clinical research with children.